PROTEST AGAINST STEREOTYPE THREATS REFLECTED IN TONI MORRISON’S THE BLUEST EYE NOVEL - Ahmad Imam Muzaqi (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
This study explores the stereotype threats portrayed in Toni Morrison’s The Bluest Eye, focusing on how racial identity and societal norms shape the lived experiences of Black characters. This study projects three main issues, namely (1) Exploring the historical background of the novel, (2) Identifying Toni Morrison’s protests against negative stereotypes, and (3) Deciphering the author's concerns about stereotype threats. This study applied qualitative data to document analysis from The Bluest Eye Novel and used a note-taking techniques. The study showed that Morrison depicted the black family conflicts emerged as a result of a lack of welfare, social discrimination, and cultural discord from his novel. She appeared in some protests against the negative stereotypes, 1) Fighting for women’s existence by calling for the right to freedom and legal protection; 2) Raising the role of the black family; 3) Claiming that black has its beauty; 4) Opposing the white-racial doctrine of educational literacy. In realistic threats, Morrison criticized life inequality, moral damage, and lack of legal protection. Meanwhile, in symbolic threats, Morrison deflected the white beauty standards and opposed literacy books that raised racial differences. Thus, Morrison explored the racial conflict by showing her empathic protest.